2017
DOI: 10.1002/ange.201706850
|View full text |Cite
|
Sign up to set email alerts
|

Alkynyl Thioethers in Gold‐Catalyzed Annulations To Form Oxazoles

Abstract: Non-oxidative,regioselective,and convergent access to densely functionalized oxazoles is realized in af unctionalgroup tolerant manner using alkynyl thioethers.S ulfur-terminated alkynes provideaccess to reactivity previously requiring strong donor-substituted alkynes such as ynamides.Sulfur does not act in an analogous donor fashion in this gold-catalyzed reaction, thus leading to complementary regioselective outcomes and addressing the limitations of using ynamides.Compared to other heteroatom-substituted al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Column chromatography (silica gel, eluting with 0−100% dichloromethane/heptane gradient) afforded the desired product as a colorless oil (644 mg, 82%). Characterization data obtained agree with the literature data: 16 1 H NMR (300 MHz, chloroform-d) δ 7.34 (d, J = 8.8 Hz, 2H), 6.82 (d, J = 8.8 Hz, 2H), 3.78 (s, 3H), 2.04 (s, 3H); 13 C{ 1 H} NMR (75 MHz, chloroform-d) δ 159.1, 132.9, 116.3, 113.9, 84.2, 79.5, 55.2, 4.3.…”
Section: ■ Experimental Sectionsupporting
confidence: 87%
“…Column chromatography (silica gel, eluting with 0−100% dichloromethane/heptane gradient) afforded the desired product as a colorless oil (644 mg, 82%). Characterization data obtained agree with the literature data: 16 1 H NMR (300 MHz, chloroform-d) δ 7.34 (d, J = 8.8 Hz, 2H), 6.82 (d, J = 8.8 Hz, 2H), 3.78 (s, 3H), 2.04 (s, 3H); 13 C{ 1 H} NMR (75 MHz, chloroform-d) δ 159.1, 132.9, 116.3, 113.9, 84.2, 79.5, 55.2, 4.3.…”
Section: ■ Experimental Sectionsupporting
confidence: 87%
“…In this strategy, the thiosulfonates 48 were commonly used as the electrophiles (Scheme 44). 58 Both the aliphatic and aromatic thio group could be well incorporated to form the C-S bond.…”
Section: Sp C-s Bond Formationmentioning
confidence: 99%
“…7 For example, Davies and coworkers showed that the use of N-acylpyridinium amine with a Au(III) precatalyst results in selective attack on the β-position of alkynyl sulfide. 8 A zinc(II)-catalyzed coupling of alkynyl thioether and isoxazole derivatives was also described by Ye's group, featuring selective α-addition and 1,2-S migration with the formation of sulfur-bearing β-keto enamide products. 9 Davies and coworkers recently reported a compelling Aucatalyzed reaction between alkynyl thioethers and isoxazole or anthranil derivatives (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few specific examples of systems can show efficient conversions when using other types of alkynes . For example, Davies and coworkers showed that the use of N -acylpyridinium amine with a Au­(III) precatalyst results in selective attack on the β-position of alkynyl sulfide . A zinc­(II)-catalyzed coupling of alkynyl thioether and isoxazole derivatives was also described by Ye’s group, featuring selective α-addition and 1,2-S migration with the formation of sulfur-bearing β-keto enamide products …”
Section: Introductionmentioning
confidence: 99%